2005
DOI: 10.1007/s00438-005-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

Sir-dependent downregulation of various aging processes

Abstract: Using a new genetic selection approach in yeast termed fitness-based interferential genetics (FIG), genes that are in an antagonistic relationship with the Sir complexes were selected. Many of the functionally well-defined genes belong to various aging processes occurring in this organism. Three genes are somehow involved in glucose utilization (HXT4,YIL107c, EMI2). Another gene, CDC25, encodes the main regulator of the cyclic AMP pathway in response to glucose. STM1 has been implicated in the control of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…cerevisiae and A . nidulans (Daniel, 2005; Bernardo et al , 2007) and also in Arabidopsis (Karve et al , 2008). Whether non-catalytic homologues of known enzymes are commonly present in other protein families is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cerevisiae and A . nidulans (Daniel, 2005; Bernardo et al , 2007) and also in Arabidopsis (Karve et al , 2008). Whether non-catalytic homologues of known enzymes are commonly present in other protein families is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal HKL proteins have divergent roles including one as a meiosis-specific transcription factor in Saccharomyces cerevisiae (Daniel, 2005) and others as regulators of a carbon starvation response in Aspergillus nidulans (Bernardo et al , 2007). Despite the reports of the presence of HKL proteins in evolutionarily diverse species, their lack of catalytic activity has made it challenging to define their functions.…”
Section: Introductionmentioning
confidence: 99%
“…EMI2 is a cytoplasmic protein that is required for induction of early meiosis-specific transcription factor IME1 and sporulation while the function and subcellular location of YLR446W is unknown (Enyenihi and Saunders 2003; Saccharomyces Genome Database, http://www.yeastgenome.org/). EMI2 has also been shown to act as an antagonist to Sir2p, a histone deacetylase involved in chromatin silencing and regulation of cell aging (Daniel 2005). Phylogenetic analysis of fungal hexokinases using the distance method showed that YLR446W, but not EMI2, clusters with HxkC and HxkD (Fig.…”
Section: Regulation Of the Hxkd Transcriptmentioning
confidence: 98%
“…The metabolic only catalysts include yeast HXK1 and glucokinase1 (Santangelo 2006), and we suggest might also include plant plastid HXKs. Among non-catalytic HKL proteins, there are two HKL proteins in S. cerevisiae (Bernardo et al 2007), one of which, EMI2, is required for induction of a meiosis-specific transcription factor (Daniel 2005). In A. nidulans, the non-catalytic proteins AnHXKC and AnHXKD both are thought not to have a role in glucose signaling, but genetic evidence indicates that instead both are negative regulators for a secreted extracellular protease during carbon starvation (Bernardo et al 2007).…”
Section: Discussionmentioning
confidence: 99%